2019
DOI: 10.1111/pce.13692
|View full text |Cite
|
Sign up to set email alerts
|

Protein lysine methylation contributes to modulating the response of sensitive and tolerant Arabidopsis species to cadmium stress

Abstract: The mechanisms underlying the response and adaptation of plants to excess of trace elements are not fully described. Here, we analysed the importance of protein lysine methylation for plants to cope with cadmium. We analysed the effect of cadmium on lysine‐methylated proteins and protein lysine methyltransferases (KMTs) in two cadmium‐sensitive species, Arabidopsis thaliana and A. lyrata, and in three populations of A. halleri with contrasting cadmium accumulation and tolerance traits. We showed that some prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…We showed that U induced a modification of the methylation pattern of some proteins, as previously observed in Arabidopsis plants treated with cadmium. 46 Also, MS/MS analysis identified that the 40S ribosomal protein RPS10C was dimethylated at Arg159 and Arg163 following U stress. This is the first evidence of methylation of this protein in plants despite the comprehensive analysis of post-translational modifications of the 80S cytosolic ribosome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that U induced a modification of the methylation pattern of some proteins, as previously observed in Arabidopsis plants treated with cadmium. 46 Also, MS/MS analysis identified that the 40S ribosomal protein RPS10C was dimethylated at Arg159 and Arg163 following U stress. This is the first evidence of methylation of this protein in plants despite the comprehensive analysis of post-translational modifications of the 80S cytosolic ribosome.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45] In support of this assumption, we have recently shown that protein Lys methylation contributes in modulating the response of Arabidopsis plants to a stress induced by cadmium. 46 Immunoblots with total soluble proteins revealed a few methylated polypeptides whereas those realized with the fractions separated by AEC showed additional methylated proteins. We further analysed the dimethylated Arg signal that was detected in a 15-20 kDa polypeptide in F100 and that was more strongly immuno-labelled in U-stressed than in control cells (Fig.…”
Section: Analysis Of Post-translational Modifications In Arabidopsis mentioning
confidence: 94%
“…(2020) showed that DNA demethylation enhances plant tolerance to Cd toxicity in A. thaliana , while Serre et al . (2020) pointed out differences in the Lys methylation of nonhistone proteins in two Cd‐sensitive species, A. thaliana and A. lyrata , and in three populations of A. halleri AU, I16 and PL22 with contrasting Cd accumulation and tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Cd on Lys-methylated proteins and KMTs were studied in A. thaliana, A. lyrata, and A. halleri, which have differential tolerance to Cd. Gene expression, protein mass spectrometric, and immunoblotting techniques revealed significant expressions in Lys-methylated proteins and regulation of genes coding KMTs by Cd (Serre et al, 2020). Interruption of KMT gene in A. thaliana displayed a significant increase in Cd tolerance in comparison with wild type plants.…”
Section: Feedback Regulation Bymentioning
confidence: 97%
“…It has been found that variability exists among different populations of A. halleri for Cd accumulation (Stein et al, 2017;Corso et al, 2018). Such an intraspecific variability has prompted Serre et al (2020) to investigate the molecular mechanisms associated with metal tolerance, especially the Lys-methylated proteins in plants. The effect of Cd on Lys-methylated proteins and KMTs were studied in A. thaliana, A. lyrata, and A. halleri, which have differential tolerance to Cd.…”
Section: Feedback Regulation Bymentioning
confidence: 99%